EFEKTIVITAS PERAN LEMBAGA NEGARA INDEPENDEN DALAM PEMBANGUNAN GOOD GOVERNANCE DI INDONESIA - Yudith Ridzkia; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2021)
The existence of state auxiliary organs also known as independent state institutions is a state institution within the Indonesian constitutional structure that is capable of creating a good governance in Indonesia. Independent state institutions were formed to carry out various aspirated changes where their existence is mentioned in the 1945 Constitution, specifically the Judicial Commission, the General Election Commission, Komnas HAM, the Public Information Commission, the National LawCommission, and the Corruption Eradication Commission (KPK). This research is intended to solve the problems about the effectiveness of the existence of independent state institutions or state auxiliary agencies for the development of good governance concept in Indonesia. This research was made through a normative manner, whereas it was derived from primary and secondary legal materials obtained from a statutory approach and an analytical approach which would then be concluded through deductive thinking. The results showed that the existence of these institutions is a few implications of the reform era which illustrates that the winds of change are bringing this nation towards real change. Since the birth of various kinds of independent state institutions, there are indications that these institutions haven’t functioned effectively and efficiently in dealing with various problems within the state. This is due to the high public suspicion of the existing state institutions because they’re considered not functioning optimally, especially in supporting the reform agenda.